On recent developments treating the exact controllability of abstract control problems - Pierri, Michelle; O'regan, Donal; Prokopczyk, Andréa (My University, 2016)
In this note we comment on an error present in the recent and extensive literature on exact controllability of abstract control differential problems. Our observations are valid for first order, second order, integro-differential and fractional differential control problems.
Keywords: Abstract control systems; Controllability; Resolvent of operators; Sectorial operators